Pendampingan Pembelajaran Akuntansi untuk Meningkatkan Kemampuan dan Keterampilan Siswa dalam Menyusun Kertas Kerja (Worksheet ) Perusahaan Jasa di SMAK St. Darius Larantuka - Maria Fatima B. Beribe; Abel Andisolo Sogen; Elisabeth Sasa Koten (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of implementing Community Service (PkM) is to overcome the problems faced by community service partners, namely difficulties in learning accounting for class XII SOS students at SMAK St. Darius Larantuka. This activity is also a follow-up to the previous study entitled